Bat Rabies in the Americas: Is Myotis the Main Ancestral Spreader? - Diego A. Caraballo; María Lorena Vico; María Guadalupe Piccirilli; Stella Maris Hirmas Riade; Susana Russo; Gustavo Martínez; Fernando J. Beltrán; Daniel M. Cisterna (Viruses, 2024)
The rabies virus (RABV) is the exclusive lyssavirus affecting both wild and domestic mammalian hosts in the Americas, including humans. Additionally, the Americas stand out as the sole region where bat rabies occurs. While carnivore rabies is being increasingly managed across the region, bats are emerging as significant reservoirs of RABV infection for humans and domestic animals. Knowledge of the bat species maintaining rabies and comprehending cross-species transmission (CST) and host shift processes are pivotal for directing surveillance as well as ecological research involving wildlife reservoir hosts. Prior research indicates that bat RABV CST is influenced by host genetic similarity and geographic overlap, reflecting host adaptation. In this study, we compiled and analyzed a comprehensive nucleoprotein gene dataset representing bat-borne RABV diversity in Argentina and the broader Americas using Bayesian phylogenetics. We examined the association between host genus and geography, finding both factors shaping the global phylogenetic structure. Utilizing a phylogeographic approach, we inferred CST and identified key bat hosts driving transmission. Consistent with CST determinants, we observed monophyletic/paraphyletic clustering of most bat genera in the RABV phylogeny, with stronger CST evidence between host genera of the same family. We further discuss Myotis as a potential ancestral spreader of much of RABV diversity.